KEUNGGULAN KOMPETITIF USAHA TERNAK SAPI POTONG DI KABUPATEN GUNUNGKIDUL - Nandang Sunandar (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2005)
The research has been conducted to find out a competitive advantage of beef cattle farming. Data used in this research was primary data collected through survey in Gunungkidul Regency, Province od Daerah Istimewa Yogyakarta. The location determination was cinducted in purposive based on population of beef cattle. The selected location was Sub District of Karang Mojo and Semanu. Total sample was defined in quota that is 240 beef cattle farmers, each 120 beef cattle farmers in Karang Mojo and Semanu. Sample selection was taken random sampling. The result suggested that (1) on the whole, without considering various production system and management that much occurred upon its actual condition, beef cattle farming in Gunung Kidul had have competitive advantage because has PCR value < 1, (2) breeding was more competitive advantage than fattening, (3) local cattle breeding has better competitive advantage than crossbreeding cattle, (4) local cattle fattening was more competitive advantage than fattening of crossbreeding cattle, (5) the competitive advantage indicates the usage of domestic resources that has been valued in actual price were quite efficient so that the beef cattle farming is proper to develop on giving economic live for its performer, and (6) the competitive advantage were acquired from the use of greenery, dedak (mixture of rice and bran), gaplek,and family force because the whole input were from field or farmer family source until there is no need cash to achieve it.